1998
DOI: 10.1144/gsjgs.155.2.0217
|View full text |Cite
|
Sign up to set email alerts
|

Rates of delta progradation during highstands: consequences for timing of deposition in deep-marine systems

Abstract: Estimated times required for 24 modern river systems to form a shelf-edge delta range from 8.5 ka to 116.5 ka, depending on fluvial sediment supply, delta width, shelf volume and shelf transport rates. These values indicate that transport of sand into deep-marine systems is likely to be significant during third-order highstands of relative sea-level. Factors such as shelf transport dynamics may slow delta progradation while submarine canyons cutting the shelf may reduce the time before deep-marine deposition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
133
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(138 citation statements)
references
References 19 publications
5
133
0
Order By: Relevance
“…The modern sediment discharge from these rivers and longshore-drift systems could fill their canyons in 400 to 2000 years (Table 1), even with sediment flux that is much reduced from their pre-Industrial levels by dams and other human activities. In the same way that previous studies have shown the excavation of incised valleys provides a sediment volume that is only 5 to 10% of the normal flux through the system (e.g., Burgess and Hovius 1998;Blum and Törnqvist 2000;Blum et al 2013), our new data show that canyons act as conduits, but their excavation does not materially contribute to the growth of submarine fans. Hence, the direct flux of sediment from hinterland source terrains through the fluvial feeder system, rather than recycling of previously stored sediments, accounts for the overwhelmingly greater part of sediment necessary for the growth and development of deep-water depositional systems.…”
Section: Submarine Canyons: the Connection Between Shelf And Deep-watsupporting
confidence: 85%
See 1 more Smart Citation
“…The modern sediment discharge from these rivers and longshore-drift systems could fill their canyons in 400 to 2000 years (Table 1), even with sediment flux that is much reduced from their pre-Industrial levels by dams and other human activities. In the same way that previous studies have shown the excavation of incised valleys provides a sediment volume that is only 5 to 10% of the normal flux through the system (e.g., Burgess and Hovius 1998;Blum and Törnqvist 2000;Blum et al 2013), our new data show that canyons act as conduits, but their excavation does not materially contribute to the growth of submarine fans. Hence, the direct flux of sediment from hinterland source terrains through the fluvial feeder system, rather than recycling of previously stored sediments, accounts for the overwhelmingly greater part of sediment necessary for the growth and development of deep-water depositional systems.…”
Section: Submarine Canyons: the Connection Between Shelf And Deep-watsupporting
confidence: 85%
“…This connection can be driven by eustatic fall, but it can also occur in tectonically active margins where the shelf is narrow (e.g., the California Borderlands), or on passive margins where a long-lived canyon has cut headward across a broad shelf (e.g., the Congo River-Zaire Canyon, the Swatch of No Ground Canyon of the Bengal system). The possibility also exists for deltas to build across the shelf and make a connection with submarine canyons even in periods of high sea level in areas of high sediment flux (Burgess and Hovius 1998;Carvajal et al 2009;Dixon et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…However, considering the relatively high-sediment supply in relation to the mainly falling base-level trend, it seems coherent to ponder that the more distal submarine fans were fed by turbidity current during both rising and falling of relative sea level (e.g., Mutti & Normark, 1991;Burgess & Hovius, 1998;Shanmugam, 2002;Dixon et al, 2012;Safronova et al, 2014;de Gasperi & Catuneanu, 2014) (Fig. 14).…”
Section: Discussionmentioning
confidence: 99%
“…Although sand transport to the deep-sea is favored by forced regressions (e.g., Muto & Steel, 2002;Helland-Hansen & Hampson, 2009), occurrence and volume of turbidites are not exclusively controlled by base-level falls (e.g., Burgess & Hovius, 1998;Carvajal & Steel, 2006;Dixon et al, 2012;Safronova et al, 2014;Berton & Vesely, 2016). Turbidites were identified in all seismic facies associations formed during base-level falls, but they are more frequently observed on the bottomset of clinoforms from association 1, in which well-developed shelf-margin deltas/shoreface deposits occur (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation